2022
DOI: 10.1111/jfpp.17225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freeze‐dried black carrot fiber addition on the physicochemical, color, sensory attributes, and mineral contents of ayran

Abstract: The present study was conducted to evaluate the production of ayran by adding freeze‐dried black carrot fiber at different ratios (0%, 0.25%, 0.5%, and 1%), followed by its storage for 14 days. It turned out that the more the amount of black carrot added, the more the amounts of Na, Mg, K, and Ca, though the sensory scores decreased. While pH, titratable acidity, viscosity, whey separation, and acetaldehyde contents of ayran were not affected by black carrot addition (p > .05), water‐holding capacity, volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Comparing the mineral analysis results of the yogurt samples with those reported by Çardak et al [53], the amounts of minerals like Ca, K, Na, and Fe appeared to be higher in their study, whereas those of Mg and Zn were lower. Additionally, it was observed that adding concentrated freeze-dried black carrot fiber at different ratios (0%, 0.25%, 0.5%, and 1%) to an ayran-containing black carrot fiber enhanced its Ca, K, Mg, Na, P, and Zn levels significantly [54]. Other authors such as Kulaitien ė et al [55] reported that the incorporation of 1% of different powders (beetroot, mulberry leaves, nettle leaves, and rosehip fruit) into yogurt bites allowed for a significant increase in the amounts of the investigated minerals (Ca, K, P, Mg, Fe, and Zn).…”
Section: Mineral Profilementioning
confidence: 99%
“…Comparing the mineral analysis results of the yogurt samples with those reported by Çardak et al [53], the amounts of minerals like Ca, K, Na, and Fe appeared to be higher in their study, whereas those of Mg and Zn were lower. Additionally, it was observed that adding concentrated freeze-dried black carrot fiber at different ratios (0%, 0.25%, 0.5%, and 1%) to an ayran-containing black carrot fiber enhanced its Ca, K, Mg, Na, P, and Zn levels significantly [54]. Other authors such as Kulaitien ė et al [55] reported that the incorporation of 1% of different powders (beetroot, mulberry leaves, nettle leaves, and rosehip fruit) into yogurt bites allowed for a significant increase in the amounts of the investigated minerals (Ca, K, P, Mg, Fe, and Zn).…”
Section: Mineral Profilementioning
confidence: 99%